Stable and metastable phases in the atomic limit of the extended Hubbard model with intersite density-density interactions - Kapcia, Konrad; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, Pl-02-668 Warsaw, Poland, 2012)
We have studied a simple effective model of charge ordered insulators. The tight binding Hamiltonian consists of the effective on-site interaction U and the intersite density-density interaction Wij (both: nearest-neighbor and next-nearest-neighbor). In the analysis of the phase diagrams and thermodynamic properties of this model we have adopted the variational approach, which treats the on-site interaction term exactly and the intersite interactions within the mean-field approximation. Our investigations of the general case (as a function of the electron concentration) have shown that the system exhibits various critical behaviors including among others bicritical, tricritical, critical-end and isolated critical points. In this report we concentrate on the metastable phases and transitions between them. One finds that the first- and second order transitions between metastable phases can exist in the system. These transitions occur in the neighborhood of first as well as second order transitions between stable phases. For the case of on-site attraction the regions of metastable homogeneous phases occurrence inside the ranges of phase separated states stability have been also determined.
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A. The Version of Record is available online at http://przyrbwn.icm.edu.pl/APP/PDF/121/a121z5p11.pdf
Keywords: charge orderings; phase separations; extended Hubbard model; atomic limit; metastability